Doctors with Asperger's: the impact of a diagnosis. (21st December 2017) - Price, Sophie; Lusznat, Rosie; Mann, Richard; Locke, Rachel
Summary: Background: Asperger syndrome (AS) is part of a spectrum of disorders encompassing difficulties with social interaction that may result in specific educational needs for doctors in training. There is currently limited research on the impact of AS on working as a doctor. Methods: This is a qualitative study using semi‐structured interviews to explore the perceptions of trainees diagnosed with AS following input from a professional support service, and the perspectives of the staff involved in their professional development. Findings: Receiving a diagnosis of AS was viewed as a double‐edged sword, allowing the development of insight into lifelong difficulties, but also creating the potential for prejudice. Understanding AS traits provided an explanation for challenges in the workplace and therefore opportunities to find solutions. Understanding AS traits provided an explanation for challenges in the workplace Discussion: This study explores the benefits and disadvantages of defining and labelling a specific professional support need for a group of trainees. It also reveals the need for improved awareness of AS amongst all clinical educators.